2017
DOI: 10.1016/j.avsg.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Duration of Brief Surgeon-Delivered Smoking Cessation Advice on Attitudes Regarding Nicotine Dependence and Tobacco Harms for Patients with Peripheral Arterial Disease

Abstract: Background Despite the recognized benefits of smoking cessation, many clinicians question if a brief smoking cessation intervention can help dedicated smokers with peripheral arterial disease understand nicotine dependence and harms related to smoking. We investigated the impact and durability of a multi-modal smoking cessation intervention on patient attitudes regarding nicotine dependence and the health effects of smoking. Methods We conducted a pilot cluster randomized trial of a brief smoking cessation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…The importance of patient education and counseling regarding smoking cessation in the perioperative period cannot be overstated. Perioperative tobacco cessation counseling has been associated with reduced postoperative complications . Cases of COPD were also found to be predictors of 30dEDRs on univariate analysis ( P = .01).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The importance of patient education and counseling regarding smoking cessation in the perioperative period cannot be overstated. Perioperative tobacco cessation counseling has been associated with reduced postoperative complications . Cases of COPD were also found to be predictors of 30dEDRs on univariate analysis ( P = .01).…”
Section: Discussionmentioning
confidence: 90%
“…Perioperative tobacco cessation counseling has been associated with reduced postoperative complications. 22 Cases of COPD were also found to be predictors of 30dEDRs on univariate analysis (P 5 .01). This follows previous research that has associated COPD in patients with head and neck cancers with increased rates of complications, 23 readmission, 24 and LOS.…”
Section: Predictors Of 30-day Emergency Department Returnsmentioning
confidence: 91%
“…Our findings build on prior work by Tang et al 21 who promote a surgeon-led script promoting referral to stop smoking resources for patients with newly diagnosed head and neck cancer. Similarly, a cluster-randomized trial by Newhall et al 22 demonstrated effectiveness of surgeon-delivered smoking cessation advice in increasing interest and awareness in smoking cessation for patients with vascular surgical problems.…”
Section: Discussionmentioning
confidence: 98%
“…A brief smoking cessation (3 months) with the help of vascular surgeon can increase patients’ desire to quit. It is also important to make patients aware of the possible long-term consequences of nicotine dependence 89. The VAPOR trial (Vascular Physician Offer and Report) designed a three-step smoking cessation intervention (advising to quit, replacing nicotine, telephone-followed quitline) and compared it to routine care.…”
Section: Discussionmentioning
confidence: 99%